Response to the comments on "Advancements in development and characterization of biodiesel: A review". Sharma YC, Singh B, Upadhyay SN. Fuel 2008;87:2355-73 by Clifford Jones - Sharma Y.C.; Singh B.; Upadhyay S.N. (My University, 2025)
[No abstract available]